Valorization of tomato peel waste: antioxidant, physicochemical properties and acceptability of dried tomato peel in beef patties - Azmi, N.; Nordin, N. A.; Abidin, S. A.S.Z.; Nizar, N. N.A.; Mutalib, S. R.A.; Ismail-Fitry, M. R. (Rynnye Lyan Resources, 2025)
In order to improve the tomato supply chain, tomato peel, a byproduct of the puree and sauce industry, was turned into dried tomato peel (DTP) powder to reduce food manufacturing waste and applied in beef patties as model food. Antioxidant properties, physicochemical properties, and acceptability of beef patties incorporated with DTP waste were determined. Four formulations; control (no DTP), 1.5% DTP, 3.0% DTP and 4.5% DTP were prepared. Antioxidant capacity was measured using 2,2-diphenyl-1-picryl hydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assay. Meanwhile, physicochemical properties such as pH, colour and texture profile were determined. Consumer’s acceptability was determined using a 9-point hedonic scale. The antioxidant capacity was reduced in both DPPH and FRAP assays whereby 3.0% DTP had the highest capacity followed by 4.5% DTP, 1.5% DTP and control. Cooking loss, drip loss, pH, peroxide value and colour of patties decreased as the amount of DTP increased. Texture profile analysis indicated that the addition of DTP significantly increased the hardness, adhesiveness and chewiness, however, there were no significant differences in springiness, cohesiveness, gumminess and resilience. The consumer acceptability test showed that beef patties with 1.5% and 3% DTP had no significant difference with control in terms of colour, taste, juiciness, appearance and overall acceptability. DTP added into beef patties at 3.0% formulation improved the antioxidant capacity. This innovation is useful to reduce waste along the food supply chain.